2009
DOI: 10.1111/j.1748-1090.2008.00072.x
|View full text |Cite
|
Sign up to set email alerts
|

Husbandry and breeding of Somali wild ass Equus africanus somalicus at Basel Zoo, Switzerland1

Abstract: Little information is available in English on the keeping and breeding of the rarest equid species, the Critically Endangered Somali wild ass Equus africanus somalicus, in captivity. The husbandry experience gained by Basel Zoo over three decades of keeping this species is summarized with particular emphasis on management, nutrition and health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 3 publications
0
7
1
Order By: Relevance
“…The two foals weight [27.65kg (first) and 31.00kg (second)] were within the range from 25 to 32kg reported by Basel Zoo (Switzerland) [19]. The cause of stillbirth (second parturition) was not clear in this study.…”
Section: --54contrasting
confidence: 37%
See 1 more Smart Citation
“…The two foals weight [27.65kg (first) and 31.00kg (second)] were within the range from 25 to 32kg reported by Basel Zoo (Switzerland) [19]. The cause of stillbirth (second parturition) was not clear in this study.…”
Section: --54contrasting
confidence: 37%
“…In our study, the change in fecal progestagens showed ovarian cyclicity and was an average of 22. [19]. In the gestation period, progestagen levels varied in different stages, with an average value of 8.9 μg/g during the first half of early pregnancy, and then sharply increasing from 67 days and 347 days after the estimated conception.…”
Section: Discussionmentioning
confidence: 99%
“…The three female asses observed were between one and two years of age at the start of observations (Female 19: 1 year, 8 months; Female 20: 1 year, 7 months; and Female 21: 1 year, 4 months). Age of puberty has not been well established for either wild or domestic asses, with published reports ranging from 9 months to 5 years [Fielding, ; Kirby, ; McCool et al, ; Mohammed, ; Pagan et al, ; Woodward, ]. However, references are not always clear on the operational definition of puberty used; that is, whether referring to age of first observed mating or birth of first foal.…”
Section: Methodsmentioning
confidence: 99%
“…Moehlman [] studied behavioral patterns of feral asses that included quantitative data on social interactions, but nothing comparable has been published for wild asses. To date, the one published report on captive Somali wild ass [Pagan et al, ] focused solely on husbandry and included only anecdotal information on behavior. The only published studies of African ass behavior in the wild [Klingel, , ; Moehlman, ] were qualitative descriptions of social organization, feeding, territorial behavior, courtship, and mating.…”
Section: Introductionmentioning
confidence: 99%
“…Selected Infectious Diseases Reported in Nondomestic Equids-cont'd Selected Noninfectious Diseases Reported in Nondomestic EquidsReproductive Characteristics of Non-Domestic Equids 6ParameterEquus hemionus Equus africanus34 Equus przewalskii Equus burchelli 19 Equus grevyi 13 Equus zebra 35 Males = 4.5 years Females = 1.5-2 years Females = 3-4 years Males = 4 years Female = 26 months Male = 42-54 months…”
mentioning
confidence: 99%